Inactivation of salmonella enterica serovar enteritidis on chicken eggshells using blue light - Hu X; Sun X; Luo S; Wu S; Chu Z; Zhang X; Liu Z; Wu J; Wang X; Liu C; Wang X (MDPI (Basel, Switzerland), 2021)
Salmonella enterica serovar Enteritidis (S. Enteritidis) is a pathogen that poses a health risk. Blue light (BL), an emerging sanitization technology, was employed for the first time in the present study to inactivate S. Enteritidis on eggshell surfaces and its influence on maintaining eggshell freshness was investigated systematically. The results showed that 415 nm-BL irradiation at a dose of 360 J/cm2 reduced 5.19 log CFU/mL of S. Enteritidis in vitro. The test on eggshells inoculated with S. Enteritidis showed that a BL dose at 54.6 J/cm2 caused a 3.73 log CFU reduction per eggshell surface and the impact of BL inactivation could be sustained in post-5-week storage. The quality of the tested eggs (weight loss, yolk index, Haugh unit (HU) and albumen pH) demonstrated that BL treatments had negligible effects on the albumen pH of eggs. However, compared to the control, BL-treated eggs showed lower weight loss and higher HU after 5 weeks of storage at 25◦C and 65% humidity and yolk index in the control group could not be determined after 5 weeks of storage. Besides, the total amino acid content of the BL-treated egg was higher than the control, exhibiting an advantage of BL irradiation in maintaining the nutrient quality of whole eggs. The current study determined the efficacy of BL against S. Enteritidis on eggshell and suggested that BL could be an effective application in maintaining the freshness and quality of eggs.
Keywords: Salmonella enteritidis; blue light; inactivation; eggshell; freshness